Architecture and design for the future internet 4WARD Project - Correia, Luis M. (Signals and Communication Technology, 2011)
Architecture and Design for the Future Internet addresses the Networks of the Future and the Future Internet, focusing on networks aspects, offering both technical and non-technical perspectives. It presents the main findings of 4WARD (Architecture and Design for the Future Internet), a European Integrated Project within Framework Programme 7, which addressed this area from an innovative approach. Today?s network architectures are stifling innovation, restricting it mostly to the application level, while the need for structural change is increasingly evident. The absence of adequate facilities to design, optimise and interoperate new networks currently forces a convergence to an architecture that is suboptimal for many applications and that cannot support innovations within itself, the Internet. 4WARD overcomes this impasse through a set of radical architectural approaches, built on a strong mobile and wireless background. The main topics addressed by the book are: the improved ability to design inter-operable and complementary families of network architectures; the enabled co-existence of multiple networks on common platforms through carrier-grade virtualisation for networking resources; the enhanced utility of networks by making them self-managing; the increased robustness and efficiency of networks by leveraging diversity; and the improved application support by a new information-centric paradigm in place of the old host-centric approach. These solutions embrace the full range of technologies, from fibre backbones to wireless and sensor networks.